Study of a soil Julidae community in Mediterranean forest (Diplopoda, Julida) (ENTOMOLOGICA SCANDINAVICA, 1997)
This work is part of a larger study on the communities of epigean and edaphic arthropods from the Pare Natural de Sant Llorenc de Munt (Barcelona, Spain). The study was performed in an experimental plot in a sclerophyllous forest of Mediterranean climate, consisting mainly of Quercus ilex and Pinus halepensis. Field sampling was performed during 25 consecutive months in order to quantify the density of Julidae. In the experimental plot (40 x 40 m), three horizons were sampled: L+F (leaf litter fall), H (humus), and A (the first five cm oft he mineral layer). Among the studied material, we found four species of Julidae: Cylindroiulus punctatus (Leach, 1815), Cylindroiulus sanctimichaelis Attems, 1927, Leptoiulus belgicus (Latzel, 1884), and Ommatoiulus sabulosus (Linnaeus, 1758), with mean densities of 39.45, 35.22, 3.79 and 0.77 ind./m(2), respectively. We didn't find significant differences in mean density between months during the study period for any of these four species. The vertical distribution along the edaphic profile was evaluated using the index of Usher. All species showed a preference for horizon H, with occasional migrations towards the deeper level A, or the shallower level L/F. The analysis of the distribution of juvenile and adult specimens indicated that the reproductive periods occurred mostly in late winter or spring, while the recruitment occurred in spring-early summer.